Meningkatkan Nilai-Nilai Moral Anak melalui Metode Cerita Di Kelompok Bermain Amanah Tlogowungu Pati - Dwi Sulistyaningrum (Universitas Al-Hikmah Indonesia, 2017)
This study aims (1) To know the moral values of children aged 3-4 years in KB Amanah Guwo Tlogowungu Pati Lesson Year 2016/2017. (2) To know the improvement of moral values of children through the method of ceritadi KB Amanah Guwo Tlogowungu Pati Lesson Year 2016 / 2017. Metode this research using classroom action research. This research is conducted in two stages, that are cycle I and cycle II. The subjects of this study are students of Amanah Playgroup Group age 3-4 Guwo Tlogowungu Pati as many as 20 students. The results of this study indicate that storytelling can improve the moral values of children carried out with two cycles, the first cycle is done by telling stories directly, sikus II is done with the book cerita. From data analysis and observation through storytelling showed an increase from pre cycle 35% children which is complete in moral values, rises in the first cycle to 60%. It means an increase of 25%. And in the second cycle increased to 85% and an increase until 60%. The results achieved in cycle II already meet the determined completion target, which is 80% of the total children, they get the value with the category of the total value of 85. The increase of this average value proves that storytelling can improve the moral values of children.